Impact of Criminal Code's Articles 263 & 264: A Critical Look at Press Freedom and Human Rights - Efren Nova; Zico Junius Fernando; Panca Sarjana Putra; Agusalim Agusalim (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
The public, human rights advocates, and media practitioners have engagedin significant debate regarding Articles 263 and 264 of the new CriminalCode (KUHP). These articles establish laws that criminalize spreadingfalse news that could cause social unrest. The punishments for spreadingsuch information vary depending on the severity and intention behind itsdissemination. Articles 263(1) and (2) differentiate between intentionallyspreading false information that the perpetrator knows is untrue andspreading information that is reasonably believed to be false. The punishmentfor this offense can be imprisonment for up to six years or a maximumfine of category V. Article 264 specifically addresses the act of spreadingfalse information that the perpetrator knows is untrue. Meanwhile, Article264 specifically addresses the act of spreading ambiguous, exaggerated,or incomplete news. Those found guilty can face a maximum penalty oftwo years in prison or a category III fine. This study utilizes normativelegal methodologies, which include statutory, conceptual, comparative,and futuristic approaches. The research design is characterized by bothdescriptive and prescriptive elements. Content analysis was conductedto evaluate the collected data. The study's findings illustrate that theprimary objective of Articles 263 and 264 of the new Criminal Code is tomaintain public order and deter riots that may arise as a consequence of thedissemination of incorrect information. Nevertheless, these provisions havebeen criticized for their potential to be used as a means to suppress pressfreedom and limit public expression, both of which are fundamental aspectsof democracy and the protection of human rights. Concerns have beenraised about the potential impact of the implementation of these articles onthe protection of press freedom as guaranteed by the Press Law.